The revival of spiritual practices: factors influencing the “seeking deities and offering prayers” behavior of China’s Generation Z on social media in an atheistic context - Wang, Jing; Balakrishnan, Balamuralithara; Wan, Xiaohui; Yu, Qirui; Ye, Qiqi (Frontiers in Psychology, 2025)
IntroductionOver the past decade, there has been a growing focus on the study of how religion and technology intersect, particularly within the field of digital religion studies. In recent years, digital religious activities have emerged on Chinese social media platforms, with the sharing and promotion of content related to religious activities becoming increasingly popular. In a country like China, which adheres to atheistic ideology, the emergence of religious activities among the Generation Z youth provides a unique case for academic research. However, there is very limited research on digital religious behavior in mainland China. This study fills this gap by extending the Theory of Planned Behavior (TPB) to predict additional influencing factors of digital religious intentions and behavior.MethodsThis study employed a quantitative design, disseminating surveys via Sina Weibo and the Douyin platform. We collected a total of 525 valid responses. This study aims to deeply explore the social and psychological factors generated by digital religious activities on social media platforms, particularly how they stimulate Chinese Generation Z youth to participate in digital religious activities.ResultsThe results show that attitudes toward digital religion, perceived behavioral control, social identity, and empathetic willingness are predictors of intentions, while social norms are not. Intentions significantly predict users’behavior on social media platforms such as Weibo and Douyin. Moreover, empathetic willingness and social identity fully mediate the effects of subjective norms, perceived behavioral control, and attitudes on intentions. Consequently, these behaviors generate impact, indicating the presence of multiple mediation effects.DiscussionUnlike the societal context of theistic nations, there is a pronounced atheistic inclination within Chinese society. Consequently, subjective norms do not influence the digital religious behaviors of Chinese youth. Among contemporary Chinese youth, participation in digital religious practices is a temporary, secular activity undertaken only as a comforting behavior when anxiety becomes unmanageable or surpasses their threshold of tolerance. In contemporary China, young people face immense pressures stemming from workplace competition, social interactions, and economic burdens. Social media offers these young individuals broader opportunities for connection, community formation, and identity construction, as well as various possibilities for organizing their social lives. Consequently, on one hand, they turn to online religious avenues, seeking understanding from others through shared experiences, thereby obtaining emotional solace and comfort. On the other hand, they look to spiritual beliefs to alleviate anxiety, resolve confusion, and gain psychological comfort through emotional exchanges. Therefore, digital religion can, to some extent, be viewed as a form of social-technological empowerment, providing contemporary youth with a new “pressure valve” to facilitate emotional relief, comfort, and tension alleviation.